The Role of the Central Java Regional Police in Overcoming Religious and Political Radicalism Crimes - Prima, Prima Prasilia Sulpa (Law Research Review Quarterly, 2024)
This study examines the role of the Police as law enforcement officers in dealing with and preventing criminal acts of radical movements with an understanding that can give rise to rebellions that have similarities with terrorism because they are categorized as two threats to the unity and security of the state through religion and politics. The factor that causes this radicalism is because the understanding of religion is still fragmented, as a result of which they feel that religion and themselves are the most correct so that they have the desire to change the current system of government and replace it with Islamic law. This research uses a literature approach, namely by collecting data from various literatures which are then used to analyze and solve the problems studied. This research focuses on the crime of radicalism committed by the Islamic State of Indonesia with the intention of overthrowing the government with the arrest of the Governor of NII and several of his staff in the Central Java Police. The findings of this study are important for law enforcers, especially the Police because as law enforcement officers the Police must have a good strategy to be able to overcome, prevent, and overcome radicalism and terrorism. With this research, it can be a very important support as a means of law enforcement to achieve legal certainty, create justice, and maintain public order.